The Impact of BI Rate, Exchange Rate, and Inflation on Broad Money in Indonesia - Hesniati, Hesniati; Koo, Felicia; Fernando, Fernando; Winardy, Jeffri; Chuadra, Wiriya Dharma (Gorontalo State University, 2022)
The purpose of this study is to develop a model and research the effect of macroeconomics which includes the BI rate, exchange rate, and inflation on the development of the broad money (M2) by using data from the last ten years from 2011-2020 and obtaining 120 data. The method used in this research is quantitative research using SPSS software as a data processing tool. The results show that the variable BI rate, exchange rate, and inflation simultaneously have a significant effect on the amount of money circulating in Indonesia in the 2011-2020 period. In addition, the inflation variable and the BI rate have a negative relationship with the broad money (M2). Meanwhile, the exchange rate has a significant positive effect on broad money (M2).